2017
DOI: 10.1021/acsbiomaterials.7b00741
|View full text |Cite
|
Sign up to set email alerts
|

Injectable, Self-Healing Chimeric Catechol-Fe(III) Hydrogel for Localized Combination Cancer Therapy

Abstract: Conventional intravenous or oral administration of a combination of chemotherapeutics displays poor bioavailability and induces undesirable systemic toxicity. Therefore, localized delivery of such chemotherapeutic combinations using polymeric hydrogels is expected to help in enhancing drug efficacy and reducing systemic toxicity. In this manuscript, we have utilized a chitosan-catechol based hydrogel (CAT-Gel) assembled through catechol-Fe­(III) coordinative interactions for localized combination therapy in mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 49 publications
(90 reference statements)
1
62
0
2
Order By: Relevance
“…More recently, Yavvari et al . showed that a chitosan‐catechol based shear‐thinning and self‐healing hydrogel assembled through catechol‐Fe(III) coordination with encapsulated chemotherapeutics, allowed sustained delivery over 40 days in murine lung and breast cancer models …”
Section: Physical Associations To Assemble Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Yavvari et al . showed that a chitosan‐catechol based shear‐thinning and self‐healing hydrogel assembled through catechol‐Fe(III) coordination with encapsulated chemotherapeutics, allowed sustained delivery over 40 days in murine lung and breast cancer models …”
Section: Physical Associations To Assemble Hydrogelsmentioning
confidence: 99%
“…154 More recently, Yavvari et al showed that a chitosan-catechol based shear-thinning and self-healing hydrogel assembled through catechol-Fe(III) coordination with encapsulated chemotherapeutics, allowed sustained delivery over 40 days in murine lung and breast cancer models. 15 With a more theoretical approach, Grindy et al demonstrated that a model system of four-arm PEG crosslinked with multiple, kinetically distinct dynamic metal-ligand complexes allowed control over the mechanical properties under load by tuning the relative concentrations of two types of crosslinkers. 155 In a new theoretical framework, modeling hydrogels with kinetically distinct crosslinks was shown to enable the separation of temporal hierarchy from spatial hierarchy.…”
Section: Electrostatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the rapid development of self‐healing materials benefited from the unique ability that they can restore the original properties and functionalities after damage, to improve their durability, safety, and longevity . Hence, the self‐healing materials have been developed for applications in various fields including structural materials, coating, soft robotics and artificial skin, and medicine engineering . As is well known, many people used the dynamic covalent and noncovalent bonds to design the self‐healing materials .…”
Section: Introductionmentioning
confidence: 99%
“…1 Hence, the self-healing materials have been developed for applications in various fields including structural materials, 2,3 coating, 4-6 soft robotics and artificial skin, [7][8][9][10][11] and medicine engineering. [12][13][14][15] As is well known, many people used the dynamic covalent and noncovalent bonds to design the self-healing materials. [16][17][18][19] So far, the self-healing materials fabricated from the dynamic covalent show high mechanical properties but sacrifice the self-healing efficiency.…”
mentioning
confidence: 99%